Specificity of the Gospel of Mark as Interpreted by Theophylact of Ohrid - Czarnuch-Sodzawiczny, Monika (Verbum vitae, 2021)
While Theophylact’s Enarratio in Evangelium Marci [Explanation of the Gospel of Mark] is known as the first commentary on the whole Gospel in Greek, the question remains: how much of Mark’s Gospel is in this Explanation? The main aim of the article is to examine whether Theophylact notices the specificity of Mark’s Gospel, or whether he is harmonizing Mark with Matthew, on which he commented earlier, or other Gospels. The analysis of the Explanation of the Gospel of Mark shows that Theophylact relates to content typical of the Gospel of Mark. He distinguishes Mark’s theology from other Gospels, recognizing at the same time the theological unity of the four Gospels. His attentiveness to the details of the narrative is evidenced by the accurate presentation of divergences and, regarding some pericopes, the lack of harmonization.